Philosophy of Markets and Price Theory in Islamic Economics: a Multidisciplinary Perspective - Mohammad Anis Sumadi; Rokhmat Subagiyo; Ahmad Khudhory; Silachi Agusta Adi Putra; Ahmad Zainal Abidin; Ahmad Qosim (Journal of Islamic Economics Perspectives, 2025)
This study critically re-examines the philosophical foundations of market and price theory in Islamic economics through a multidisciplinary integration of psychology, Islamic jurisprudence (fiqh siy?sah), and sociology. Psychology elucidates how motivation, perception, and decision-making are shaped by Islamic values, while fiqh siy?sah provides the legal and normative framework that ensures justice, ethical conduct, and compliance with Islamic law in regulating market mechanisms. Sociology complements these perspectives by explaining how social structures, cultural norms, and collective behavior influence market interactions. Through this synthesis, the study constructs a holistic framework that transcends the technical dimensions of conventional market theory by embedding moral, social, and behavioral ethics into economic analysis. Using a literature-based narrative method, this research integrates the epistemological strengths of each discipline without diminishing their distinct paradigms. The novelty lies in offering a unified model of Islamic market analysis that incorporates moral reasoning, social dynamics, and behavioral psychology into price determination and market equilibrium. Findings reveal that this multidisciplinary approach enriches theoretical and practical understanding of markets as both economic and moral institutions, balancing efficiency with justice and social responsibility. The study concludes that integrating ethical, psychological, and sociological dimensions leads to a more comprehensive and equitable model of Islamic market behavior, contributing to the advancement of Islamic economic theory, value-driven research methodologies, and sustainable policy design aligned with the maq??id al-shar??ah—the higher objectives of Islamic law.